Feeding MGA to grazing heifers - Corah, L.; Brazle, F.; Davidson, Jeffrey L. (Kansas State University. Agricultural Experiment Station, 2011)
Feeding MGA to grazing heifers suppressed estrus but did not improve gain.
Keywords: Beef; MGA; Heifers